ChemInform Abstract: Organocatalytic Enantioselective Aza‐Michael Addition of Purine Bases to α, β‐Unsaturated Ketones. Issue 15 (25th March 2013) - Wu, Hao; Tian, Zhiqing; Zhang, Lili; Huang, Yaodong; Wang, Yongmei
Abstract The corresponding Michael adducts are obtained in good yields and high enantioselectivities.